Circular drawings of rooted trees - Guy Melançon; Ivan Herman (Centrum voor Wiskunde en Informatica, 1998)
We describe an algorithm producing circular layouts for trees, that is drawings, where subtrees of a node lie within circles, and these circles are themselves placed on the circumference of a circle. The complexity and methodology of our algorithm compares to Reingold and Tilford's algorithm for trees. Moreover, the algorithm naturally admits distortion transformations of the layout. This, added to its low complexity, makes it very well suited to be used in an interactive environment.